Surveillance of Bosniak IIF renal cysts: Rationalising follow-up policy. (November 2016) - Raslan, Mutie; Tolofari, Sotonye K; Bromby, Adam; Costa, Diogo; Maddineni, Satish B; Cowie, Alistair; O'Dwyer, Catherine; O'Flynn, Kieran J
Objectives: To assess the clinical outcomes of patients diagnosed with Bosniak IIF renal cysts, in order to rationalise our surveillance policy. Patients and methods: We identified all patients diagnosed with a Bosniak IIF cyst between September 2011 and September 2014. Patient demographics, duration, frequency and modality of surveillance were recorded. Changes in the size, appearance or characteristics of the cyst(s) were recorded, as well as any subsequent surgery and histology. We also estimated the overall cost of imaging and follow up. Results: We identified 198 patients. The majority of IIF cysts were incidental findings (86.5%), with 56% of cysts > 3 cm at diagnosis. Median follow-up time was 27 months. We found that 98% of cysts were unchanged in their Bosniak score and 66% did not change in size. We followed up on 86 patients (43%) beyond two years: None had radiological progression. Four patients (2%) underwent partial nephrectomy secondary to radiological progression: One (0.5%) had histological malignancy. Features of malignancy were noticed in the first 24 months of the follow-up period. Conclusions: Radiological progression of Bosniak IIF cysts is low and progression to malignancy lower still, typically occurring within 24 months of diagnosis. Our data suggested that ceasing radiological follow-up surveillance after a minimum of two years of stable surveillance could be considered. Rational follow-up protocols for Bosniak IIF cysts would have significant cost-saving implications for the National Health Service (NHS) and alleviate pressure on radiology and urology services.